A produção, o consumo e a composição química dos alimentos orgânicos - Ferraz, Ana Paula Rodrigues [UNESP]; Malheiros, Jessica Moraes [UNESP]; Cintra, Renata Maria Galvao de Campos [UNESP] (My University, 2013)
The data showed in this review exposes basic aspects that define organic foods and some factors that influence consumption by the population, ie, its production in the country and the motivations for the consumption of food produced in this system . This way of production, originated in the early decades in the 20th century, nowadays involves environmental, social and health aspects. Although the environment is a more evident aspect than other ones, economic output and potential beneficial to health are discussed further in this description about organic foods. Brazil, has excelled in the growth of this type of farming, however holds the 6th position in the world and 2nd producer in Latin America, with grains and vegetables being the main products, although the livestock reaches the largest area. The consumption of these products is primarily motivated by the perception of organic food as healthier than other kinds of food. However, there are no conclusive studies about better nutritional value, where nutrient concentrations are often unchanged. In contrast the presence of more phytochemicals compounds and reduced pesticides’ content in vegetables, and lipid profile in animal products can justify the health benefits of the products obtained from the organic production system.

Os dados apresentados expõem aspectos básicos que definem os alimentos orgânicos e alguns fatores que influenciam no consumo pela população, ou seja, sua produção no país e as motivações para o consumo dos alimentos produzidos nesse sistema. Este tipo de produção, originado nas primeiras décadas no século 20, envolve atualmente aspectos ambientais, sociais e da saúde. Embora a preocupação com meio ambiente, seja muito evidenciada, a produção econômica e o potencial benéfico à saúde são os mais discutidos nesta descrição sobre os alimentos orgânicos. O Brasil, tem se destacado no crescimento deste tipo de agropecuária, no entanto ocupa a 6ª posição no mundo, e 2º produtor na América Latina, sendo grãos e hortaliças os principais produtos, embora a pecuária atinja a maior área. O consumo destes produtos é motivado principalmente pela percepção do alimento orgânico como mais saudável. No entanto, as pesquisas não são conclusivas sobre o maior valor nutricional, sendo concentração de nutriente, muitas vezes, inalteradas. Em contrapartida a presença de fitoquímicos e reduzido teor de pesticidas em vegetais, e o perfil de lipídios em produtos animais podem justificar os benefícios à saúde dos produtos obtidos do sistema orgânico de produção.
The production, intake and the chemical composition of organic foods
Keywords: Organic foods; Nutritional value; Organic agriculture; Alimentos orgânicos; Valor nutricional; Agricultura orgânica